The impacts of mind-wandering on flow: Examining the critical role of physical activity and mindfulness - Deng, Yu-Qin; Zhang, Binn; Zheng, Xinyan; Liu, Ying; Wang, Xiaochun; Zhou, Chenglin (Frontiers in Psychology, 2022)
Background: Individuals with mind-wandering experience their attention decoupling from their main task at hand while others with flow experience fully engage in their task with the optimum experience. There seems to be a negative relationship between mind-wandering and flow. However, it remains unclear to what extent mind-wandering exerts impact on flow. And it is also elusive whether physical activity and mindfulness, which are as important factors affected individuals’ attentional control and psychological health, are beneficial in explaining the association between mind-wandering and flow. The current study investigated the relationship between mind-wandering and flow, and the potential mediation effects of physical activity and mindfulness in this association. Methods: A cross-sectional exploratory study design, including multiple scales such as the Mind-Wandering Questionnaire (MWQ), the International Physical Activity Questionnaire Short Form (IPAQ), Mindfulness Attention and Awareness Scale (MAAS) and the Short Dispositional Flow Scale (S-DFS), was applied. Descriptive statistics and bivariate correlation coefficients were applied in the analysis of these data. Multiple mediation model was used to examine the relationships between mind-wandering, flow, physical activity and mindfulness. Results: Mind-wandering was inversely associated with physical activity, mindfulness and flow, respectively; and flow was positively related to physical activity and mindfulness, respectively. Moreover, multiple mediation results demonstrated that physical activity and mindfulness respectively mediated the relationship between mind-wandering and flow. Conclusions: These findings are helpful to understand how our minds attend to the present-moment, and the crucial roles of physical activity and mindfulness in the association between mind-wandering and flow. An implication of these is the possibility that the effective strategies aimed at enhancing both levels of physical activity and mindfulness are needed to reduce the negative impact of mind-wandering on flow.